2018
DOI: 10.3389/fpls.2018.01235
|View full text |Cite
|
Sign up to set email alerts
|

A Transcript and Metabolite Atlas of Blackcurrant Fruit Development Highlights Hormonal Regulation and Reveals the Role of Key Transcription Factors

Abstract: Blackcurrant fruit collected at six stages of development were assessed for changes in gene expression using custom whole transcriptome microarrays and for variation in metabolite content using a combination of liquid chromatography-mass spectrometry and gas chromatography-mass spectrometry. Principal components analysis demonstrated that fruit development could be clearly defined according to their transcript or metabolite profiles. During early developmental stages, metabolite profiles were dominated by amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 132 publications
1
3
0
Order By: Relevance
“…In our previous research, the weather condition in the last months of growth before harvest showed special importance for blackcurrant fruit development, , since several main primary (sugars) and secondary (anthocyanins) metabolites start accumulating in the last stage of ripening of blackcurrant . In the present study, exceptionally high temperatures including both maximum day time and minimum night time temperatures were observed from mid-July to mid-August of year 2014, which was the last month before harvesting (Supplemental Table 4).…”
Section: Resultssupporting
confidence: 56%
“…In our previous research, the weather condition in the last months of growth before harvest showed special importance for blackcurrant fruit development, , since several main primary (sugars) and secondary (anthocyanins) metabolites start accumulating in the last stage of ripening of blackcurrant . In the present study, exceptionally high temperatures including both maximum day time and minimum night time temperatures were observed from mid-July to mid-August of year 2014, which was the last month before harvesting (Supplemental Table 4).…”
Section: Resultssupporting
confidence: 56%
“…This can be explained by the features of the secondary metabolism of black currant: raspberry plants are characterized by a significant content and variability of the flavonoid complex. Unlike raspberry, black currant plants with relatively low flavonoid concentrations contain significant amounts of catechins, leukoanthocyanidins and chlorogenic acid conjugates [Jarret et al, 2018]. Thus, the enzymatic system of raspberry is better balanced for quercitin transformation and glucosylation with the formation of a wide range of diverse glucosides.…”
Section: Resultsmentioning
confidence: 99%
“…The nutritional and medicinal values of currant fruits are indisputable, and have stimulated research on the synthesis of secondary metabolites in fruits. Several genetic studies related to fruit ripening and secondary metabolite synthesis have been performed based on RNA transcripts [ 18 , 21 , 22 ]. Our main attention in this study was concentrated on the ecological aspect of plant cultivation since BRV pathogen and BRD cannot be treated and cause great economic losses.…”
Section: Discussionmentioning
confidence: 99%